Tight junction protein ZO-1 in Kawasaki disease - Wan-Tz Lai; Hung-Chang Lee; Ying-Hsien Huang; Mao-Hung Lo; Ho-Chang Kuo (BMC, 2021)
Abstract Background Kawasaki disease (KD) is a form of systemic febrile vasculitis that is complicated with coronary artery lesions (CAL). The tight junctions that maintain the intestinal barrier also play a role in systemic inflammatory diseases. Serum zonula occludens-1 (ZO-1) expression was found to be significantly lower in asthmatic patients, and another study reported that elevated systemic ZO-1 was positively correlated with inflammation in cirrhotic patients. A murine model of KD vasculitis demonstrated that vasculitis depended on intestinal barrier dysfunction, which is maintained by tight junctions. In this study, we aimed to investigate the role of the tight junction zonula occludens-1 (ZO-1) in the treatment response of intravenous immunoglobulin (IVIG) and the occurrence of CAL formation in KD patients. Methods We enrolled 40 KD patients, 12 healthy controls, and 12 febrile controls in this study. The serum levels of tight junction ZO-1 were determined by enzyme-linked immunosorbent assay. Results The serum ZO-1 level was higher in the fever control group but did not reach a statistical significance. KD patients who received a second dose of IVIG treatment due to initial IVIG unresponsiveness had a higher serum levels of tight junction ZO-1, but without statistical significance (2.15 ± 0.18 vs. 2.69 ± 0.31 ng/mL, p = 0.058). KD patients who developed a CAL demonstrated a significant lower serum tight junction ZO-1 levels than KD without CAL formation (1.89 ± 0.16 vs. 2.39 ± 0.15 ng/mL, p = 0.027). After multiple logistic regression analysis, ZO-1 levels [(95% confidence interval (CI): 0.058 ~ 0.941, odds ratio (OR) = 0.235, p = 0.041)] showed as the risk factor for CAL formation. Conclusion Serum levels of tight junction ZO-1 levels were lower in KD patients than fever controls and associated with CAL formation.